A Optimizing The Role of Sharia Banking Through Cashless Services to Support Halal Tourism in Purwokerto - Rizqinuru Tami (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: This research aims to understand and explain the potential extent of cashless usage in the tourism of Taman Mas Kemambang in developing halal tourism in Indonesia. Method: This study employs a qualitative approach with a descriptive method that serves to provide an overview of information derived from the subjects and objects of the research. Result: The role of Islamic banking is crucial in the development of halal tourism because Islamic banking can enhance the national economy and the need for transactions that adhere to Islamic principles. One of the supportive functions of Islamic banking in the development of halal tourism is providing non-cash payments (cashless). The utilization of cashless payments at Taman Mas Kemambang is not fully optimized, although the implementation of cashless is used in certain areas of the tourist attraction. Contribution: This is expected to increase the adoption of cashless payments and boost the revenue of the tourist attraction because many tourists understand the benefits of cashless transactions and are attracted to the offers provided.